Analysis of The Level of Income Inequality in East Java Province for The Period 2009 - 2023 - Aditya Pratama; Moehammad Fathorrazi; Duwi Yunitasari (International Journal of Economics and Management Sciences, 2025)
This study analyzes the level of economic development disparity among regions in East Java Province during the period 2009–2023 using the Klassen Typology approach. The study aims to map the classification of regions based on economic growth rates and per capita GRDP to identify spatial disparities among the 38 districts/cities in the province. The analysis results indicate significant inequality, with regions such as Surabaya, Sidoarjo, and Gresik consistently categorized as advanced and rapidly growing areas (Quadrant I), while regions such as Sampang, Pamekasan, and Bondowoso fall into the underdeveloped category (Quadrant IV). This phenomenon shows that the economic spillover effect from growth centers to surrounding regions remains suboptimal and suggests the need for spatially-based policy interventions. This study provides important implications for formulating more inclusive regional development policies and recommends further quantitative analysis to identify the determinants of inequality in greater depth.